The United States' Response to Humanitarian Refugee Obligations: Inconsistent Application of Legal Standards and Its Consequences - Andrea Freiberger (Washington University Journal of Law & Policy, 2010)
In 1948, the countries of the United Nations ("U.N.") adopted the Universal Declaration of Human Rights ("Declaration"). The Declaration formally asserted the right to seek and receive asylum from persecution. At the 1951 Convention Relating to the Status of Refugees ("1951 Convention"), this right was developed into the principle of non-refoulement, whereby signatories agreed not to return anyone to a country in which there was a danger of persecution. Although the principle of non-refoulement requires countries to give legal status to refugees within their borders, countries have discretion in determining who meets the definition of a refugee. By altering how refugee status is determined, countries can, in effect, control and limit whom they admit and the humanitarian obligation they assume. This control is of great interest to the United States, which has historically been opposed to accepting unquantifiable and uncontrollable obligations. This Note seeks to draw attention to the intentional application of different standards for refugee determinations and proposes a fairer alternative to achieving the interests of the United States. Part I provides general background on the refugee issue. Part I.A discusses the different aspects of international refugee law. Part I.A.1 describes the humanitarian concerns associated with refugees and their plight. Part I.A.2 details the formation of the United Nations High Commission for Refugees ("UNHCR") as an international response to these concerns. Part I.B discusses the practical solutions currently used to handle protracted refugee situations, including refugee camps, voluntary repatriation, integration, and resettlement, and further addresses the duty of non-refoulement and the disparity in obligations this creates for different countries. Part I.C examines the United States' relationship with refugee situations, and looks in particular at its asylum policy, its resettlement policy, and the degree to which it fulfills its humanitarian obligations. Part II analyses the United States' policies toward refugees, specifically comparing the legal standards used for adjudication in domestic applications for asylum with those used in overseas applications for resettlement. It concludes that the United States policy achieves predictability, but (1) runs contrary to the spirit of non-refoulement, (2) increases the burden of unpredictability for other countries, and (3) increases inconsistent adjudication. Part III presents a proposal that would help to achieve predictability while eliminating some adverse effects of the current system.
Keywords: Refugee resettlement; Immigration status; Human rights; United Nations. General Assembly. Universal Declaration of Human Rights; Humanitarian aid; International obligations; Refoulement; Refugees; Right of asylum; United Nations Convention Relating to the Status of Refugees; International